Observation of curling effects in tubular and planar graphene-like structures by pyrolysis of ferrocene/dichlorobenzene mixtures - Boi, F.; Guo, J.; Medranda, D.; Borowiec, J.; Liu, D.; Wang, Shaobin; Zhang, X.; He, Y.; Xiang, G. (2018)
© 2018 Elsevier Ltd In this work, we investigate the morphological and structural properties of carbon nanostructures fabricated by means of chemical vapor deposition (CVD) methods in the presence of controlled quantities of Cl-containing precursor and ferrocene. We report the observation of a structural transition from tubular-like carbon nanotube (CNT) morphology into planar few-layers graphite in experiments involving the pyrolysis of ferrocene and dichlorobenzene mixtures. An unusual intermediate curling-like mechanism in the walls of the as-grown CNTs is found when intermediate quantities of dichlorobenzene are used. This unusual phenomenon vanishes for high quantities of dichlorobenzene, where the nucleation of planar few-layers graphene-like structures directly connected to micrometer-scale Fe3C particles is found. Such morphological variation is investigated by means of both scanning electron microscopy (SEM) and transmission electron microscopy (TEM), whereas the structural variation of the obtained structures is analyzed through X-ray diffraction and Raman spectroscopy techniques.